VOLATILITAS NILAI TUKAR DAN PERDAGANGAN INTERNASIONAL - Sri Nawatmi (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
The purpose of this study is to estimate the effect of exchange rate volatility on international tradein Indonesia. The measure of volatility show that the exchange rate has ARCH and GARCHeffect. So, volatility of the exchange rate influenced by current and previous exchange ratevolatility.Sum ofARCH and GARCH coefficient show that the exchange rate has persistentvolatile. Estimation result indicate that exchange rate volatility is not significant. While, GDPworld and GDP Indonesia influencepositivesignificant on international trade, not only in shortterm but also in long term.Key Words: volatility, ARCH, GARCH, Persistent volatile, international trade, exchange rate, andGDP